Nurse work engagement impacts job outcome and nurse-assessed quality of care: model testing with nurse practice environment and nurse work characteristics as predictors - Van Bogaert, Peter; van Heusden, Danny; Timmermans, Olaf; Franck, Erik (Frontiers in Psychology, 2014)
Key words: burnout, job satisfaction, nurse retention, nurse practice environment, quality of care, acute health care, structural equation modelling. Aim: To explore the mechanisms through which nurse practice environment dimensions are associated with job outcomes and nurse-assessed quality of care. Mediating variables tested included nurse work characteristics of workload, social capital, decision latitude, as well as work engagement dimensions of vigor, dedication and absorption. Background: Understanding to support and guide the practice community in their daily effort to answer most accurate complex care demands along with a stable nurse workforce are challenging. Design: Cross-sectional survey. Method: Based on previous empirical findings, a structural equation model designed with valid measurement instruments was tested. The study population was registered acute care hospital nurses (N = 1201) in two independent hospitals and one hospital group with six hospitals in Belgium. Results: Nurse practice environment dimensions predicted job outcome variables and nurse ratings of quality of care. Analyses were consistent with features of nurses’ work characteristics including perceived workload, decision latitude, and social capital, as well as three dimension of work engagement playing mediating roles between nurse practice environment and outcomes. A revised model adjusted using various fit measures explained 60% and 47% of job outcomes and nurse-assessed quality of care, respectively. Conclusion: Study findings show that aspects of nurse work characteristics such as workload, decision latitude and social capital along with nurse work engagement (e.g. vigor, dedication and absorption) play a role between how various stakeholders such as executives, nurse managers and physicians will organize care and how nurses perceive job outcomes and quality of care.